2017
DOI: 10.1111/fcsr.12201
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students’ Perceived Success in Attainment of Course Objectives in a Retail Merchandising Class

Abstract: This study assesses student perceptions of the effectiveness of educational approaches and assessment techniques for an introductory retail merchandising course designed using the Biggs model (1999) of constructive alignment for curriculum development. Data were collected using an online survey that was developed to evaluate students’ attitudes toward educational approaches and assessment techniques and their perceived success in attainment of course objectives. Regression results showed those students’ attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Colleges and universities should take steps toward improving the education (Sadachar, Jablon, Niehm, & Hurst, 2017) and future employability and workplace readiness of their graduates. Providing programs that expose students to the skills needed for workforce and industry, which include teamwork, communication, problem‐solving, critical thinking, and creativity, will produce competitive talent at the state, national, and global levels (Chida & Brown, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Colleges and universities should take steps toward improving the education (Sadachar, Jablon, Niehm, & Hurst, 2017) and future employability and workplace readiness of their graduates. Providing programs that expose students to the skills needed for workforce and industry, which include teamwork, communication, problem‐solving, critical thinking, and creativity, will produce competitive talent at the state, national, and global levels (Chida & Brown, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers examined instructors' perspectives, such as Rehm and Allison (2006), who explained that of family and consumer sciences instructors who utilize guest speakers, 72.5% perceived their effectiveness as high or very high. Others analyzed student perceptions, like Jimenez-Silva et al (2019), who found that education students "generally stated that they had benefitted from the guest speakers" (p. 9), and Sadachar et al (2017), who concluded that retail student attitudes towards assessment techniques, including reflections on guest speaker presentations, are significant predictors of perceived success in attaining course objectives. Karns (2005) compared marketing student perceptions in 1993 and 2004: In 1993, "guest speakers were found to be the most preferred learning activity" and were considered among the most effective as well (p. 164).…”
mentioning
confidence: 99%
“…The literature on guest speakers encompasses a wide range of disciplines, including chemistry (Zheng et al, 2018), education (Caukin & Brinthaupt, 2017), foreign languages (Albirini, 2009), instructional technology (Hemphill & Hemphill, 2007), law (Payne et al, 2003), management (Eveleth & Baker-Eveleth, 2009), mass communication (Merle & Craig, 2017), nutrition (Conklin et al, 2005), psychology (Glenwick & Chabot, 1991), and tourism and hospitality (Casado, 2000). While Sadachar et al (2017) included a cursory mention of guest speakers in an apparel merchandising class and addressed textile and apparel guest speakers solely through the lens of the virtual modality, no academic research has been discovered that investigated these students' perceptions and expectations of industry guest speakers in general. In response to this dearth of research, this study was developed, employing established qualitative research methods to explore student perceptions of industry guests who speak during a single session of fashion or apparel classes, to address the research question: "What value do students taking fashion and apparel courses find in industry guest speakers?"…”
mentioning
confidence: 99%
“…As such, the phenomenon of virtual guest speaker visits to college classrooms deserves greater investigation. Moreover, like other textile and apparel scholars (e.g., Butler et al, 2005; Byun et al, 2012; Karpova et al, 2011; Sadachar et al, 2017), the researchers believe that the input of those who are intended to reap the most benefit from pedagogical techniques deserves to be examined. Therefore, the purpose of this study was to explore virtual industry speaker visits from the viewpoint of college students, with the overarching question framing this research being, “What are student perceptions of virtual guest speakers?” The ultimate objective is to provide results that will help instructors in textile and apparel classrooms to optimally make use of special guests in their own courses.…”
mentioning
confidence: 99%